Cross-country IPOs: What explains differences in underpricing? - Banerjee, Suman; Dai, Lili; Shrestha, Keshab (Journal of Corporate Finance, 2011)
We study the impacts of country-level information asymmetry, investors' home-country bias, effectiveness of contract enforcement mechanisms, and accessibility of legal recourse on IPO underpricing in 36 countries around the globe. We find evidence consistent with all four of our hypotheses. First, we find a positive and significant effect of country-level information asymmetry on IPO underpricing. Second, our empirical evidence is consistent with the agency-cost-based explanation of IPO underpricing. We find that lower cost to entice the block holders, measured by domestic investors' home-country bias, reduces IPO underpricing. Third, we find that effective contract enforcement mechanisms help to reduce IPO underpricing. Finally, we find a positive relation between the accessibility of legal recourse and IPO underpricing.